KARAKTERISTIK FISIKOKIMIA BRIKET ARANG BATANG KELAPA SAWIT DENGAN PENAMBAHAN ARANG TEMPURUNG KELAPA - Hakim Santo; Vonny Setiaries Johan; Yelmira Zalfiatri; Yanti Nopiani (Fakultas Pertanian Universitas Riau, 2023)
Oil palm trunks and coconut shells are biomass waste that can be used to make charcoal briquettes as an alternative energy source since they contain lignin and cellulose. The goal of this study was to find the optimum briquette character from a combination of oil palm trunk charcoal and coconut shell charcoal. This study employed a completely randomized design (CRD) with five treatments and three replications. In this investigation, the ratios of oil palm trunk to coconut shell charcoal were 90:10, 80:20, 70:30, 60:40, and 50:50. The data was statistically examined using analysis of variance (ANOVA) and Duncan’s New Multiple Range Test (DNMRT) at the 5% level. The study revealed that the ratio of oil palm trunk and coconut shell charcoal had an effect on specific gravity, moisture content, fixed carbon content, ash content, and calorific value. Briquettes (50:50) with a density of 0.77 g/cm3, a water content of 4.07%, a volatile content of 14.52%, an ash content of 6.25%, a carbon content of 75.14%, and a calorific value of 7,998.07 cal/g were the best treatment.